Arabic as a Bridge for Scientific and Technological Literacy in the Islamic World (International Forum of Researchers and Lecturers, 2025)
Arabic has long served as the lingua franca of Islamic civilization, functioning not only as the language of the Qur’an but also as a powerful medium for scientific inquiry and technological advancement. During the Golden Age of Islam, Arabic emerged as the dominant language for translating, preserving, and expanding knowledge across various disciplines, including medicine, astronomy, engineering, and mathematics. This article examines the central role of Arabic as a bridge for scientific and technological literacy in the Islamic world, both historically and in contemporary contexts. Through a conceptual and historical review, the study emphasizes how Arabic facilitated epistemological integration between faith and reason, particularly through renowned institutions such as Bayt al-Hikmah and the contributions of influential scholars like Al-Kindi, Ibn Sina, and Al-Jazari. Their works demonstrate that Arabic was not merely a communication tool but also a vehicle for critical thinking, creativity, and interdisciplinary synthesis. In the modern era, however, Arabic faces significant challenges in retaining its role within global scientific discourse, including the dominance of English and other foreign languages, the fragmentation of Islamic education, and the limited integration of modern sciences into Arabic-language curricula. Addressing these challenges, the paper proposes a revitalization of Arabic instruction that aligns linguistic mastery with scientific and technological competency. This integrative approach combines traditional Islamic epistemology with contemporary educational models, enabling students to engage with both religious heritage and modern innovation. The study concludes that Arabic remains a vital link between spiritual tradition and technological progress in the Muslim world. By strategically reforming educational practices to emphasize both scientific literacy and linguistic proficiency, Arabic can once again serve as a dynamic instrument for global intellectual contribution.